Pāli as the Language of Buddhist Scripture - Tri Saputra Medhacitto (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This research aims to analytically examine the Pāli language as the language of the Buddhist sacred texts. This research is carried out by library method with content analysis as its primary approach. The data are gathered from various literary sources such as journals, books and relevant articles related to the research topic. As result, the chronology of the Pāli as the sacred language of Buddhist text can be understood. In early period, the term Pāli did not indicate as a language, but it refered to the texts or Buddhist scripture. Pāli is defined as the texts or scripture (pāṭhe iti pi pāḷi) which means “that which protects.” It is called Pāli because it protects the teaching (pāḷīti atthaṃ pāletīti pāḷi). Therefore, the term Pāli is considered synonymous with terms Buddhavacana, Tipiṭaka, Tanti, and Pariyatti. The language had been used by the Buddha when delivering the teachings was identified as Māgadhī. Pāli literature such as commentaries and chronicles hightlight that Pāli as Māgadhī, Māgadhānirutti or Māgadhikabhāsā which was the language spoken by the Buddha during his lifetime. In conclusion, at the beginning Pāli means the scripture, but later it came to be recognized as the language of the scripture.